From participants to citizens? Democratic voting rights and naturalization behavior - Michaela Slotwinski; Alois Stutzer; Pieter Bevelander (ZEW - Leibniz-Zentrum für Europäische Wirtschaftsforschung, 2020)
We study the causal effect of the possibility to vote on foreigners propensity to naturalize, a key indicator of successful integration. Based on Swedish administrative data and an institutional setting producing a quasi-random assignment of the eligibility to vote, we find that the overall effect depends on the composition of the migrant population. For immigrants from places with poor living conditions, we observe that the experience of non-citizen voting rights substantially increases their propensity to naturalize. In contrast, for those coming from places with a high standard of living, the same experience reduces it. Both reactions clearly reveal that individuals assign a positive value to formal democratic participation rights. While the behavior of the former group is likely dominated by the motivational force inherent in the possibility to participate, the behavior of the latter group reflects the devaluation of formal citizienship if it is decoupled from democratic rights.
Keywords: D02; J15; K37; 330; citizenship; migration; naturalization; value of voting; voting rights